2021
DOI: 10.6018/educatio.463821
|View full text |Cite
|
Sign up to set email alerts
|

Aprender conectados: un estudio sobre las redes personales de aprendizaje de estudiantes universitarios

Abstract: Entender como aprenden los estudiantes en la actualidad es de vital importancia para la toma de decisiones. En este sentido, la incorporación de las TIC está modificando las dinámicas de enseñanza y aprendizaje tanto formales como no formales e informales. El objetivo de este estudio es analizar las interacciones a través de diferentes recursos tecnológicos que contribuyen a la formación de estudiantes universitarios. Los entornos personales de aprendizaje (PLE) son considerados como un entramado de herramient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(13 reference statements)
0
4
0
3
Order By: Relevance
“…The findings reveal a lack of digital competences linked to ICT-mediated learning activities in the context of students’ PLEs. These results are particularly relevant in the current pandemic situation, as they reveal a picture that points to a decline in the possibilities of self-directed learning with the use of ICT, due to the forced migration to virtual contexts that has taken place in the vast majority of higher education institutions (García-Martínez et al, 2021b). In any case, in addition to the difficulties, limitations and deficiencies caused by the availability and use of ICT, the results obtained also call for reflection on the level of mastery of the strategies used by university students to respond to questions about how, who and where to learn, whether in the formal, non-formal or informal environments.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The findings reveal a lack of digital competences linked to ICT-mediated learning activities in the context of students’ PLEs. These results are particularly relevant in the current pandemic situation, as they reveal a picture that points to a decline in the possibilities of self-directed learning with the use of ICT, due to the forced migration to virtual contexts that has taken place in the vast majority of higher education institutions (García-Martínez et al, 2021b). In any case, in addition to the difficulties, limitations and deficiencies caused by the availability and use of ICT, the results obtained also call for reflection on the level of mastery of the strategies used by university students to respond to questions about how, who and where to learn, whether in the formal, non-formal or informal environments.…”
Section: Discussionmentioning
confidence: 98%
“…This is the component with the lowest scores on the PLEAS scale and, therefore, the one that needs further development, especially given the importance of these aspects in the PLE framework. There is evidence of a lack of contact with professionals in the area of study, which weakens online interactions, as well as limited access to multiple resources and materials, missing out on the possibility of being the protagonists of their own learning (Jerez-Naranjo & Barroso-Osuna, 2020) or even the creation of personal learning networks (García-Martínez et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the concept, theory, and implications of the design of pedagogical processes and learning ecosystems, in the conclusion that the use of PLE enables the creation of online learning networks that support students as partners, creators, and entrepreneurs, as well as agents of their learning [20]. Recent studies have shown that students interact more with peers and teachers through mobile communication and email; in online learning, enriching PLE is generally an essential step in learning [21].…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, el Perú en marzo del 2020 fue detectado la enfermedad del nuevo coronavirus, iniciando así una grave crisis sanitaria que ocasionó cambios en el sistema educativo (Taype & Amado, 2020). Bajo esta perspectiva las instituciones educativas de nivel superior universitarios y técnicos, se vieron en la necesidad de renovar de una enseñanza presencial a la virtualidad, para poner en práctica el confinamiento social, que busca reducir el contagio de la pandemia Covid-19, es entonces que la utilización de las TIC se fue transformando el funcionamiento de las actividades de enseñanza y aprendizaje (Echegaray, 2021;García-Martínez et al, 2021).…”
Section: Introductionunclassified